The Effect Of Tax Office Service Quality And Taxpayer Income On Land And Building Tax Compliance - Nela Dharmayanti (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2023)
The purpose of this study is to examine the effect of the tax office's service quality and the taxpayer's income on the compliance variable for paying Land and Building Tax partially and simultaneously. This type of research is classified as qualitative research that is quantified. The population in this study is the Periuk Village community listed in the tax payable notification letter (SPPT) totaling 2,172 people with a sample of 96 people. This study uses the Slovin formula as a sampling approach. Multiple regression is the data analysis approach used. The findings of this study reveal that while the quality of the tax office's service has no significant effect on compliance with Land and Building Tax, taxpayer income has a considerable favorable effect on adherence. The tax office's service quality and the taxpayer's income, either separately or in combination, significantly impact compliance with Land and Building Tax